Reversibility of adverse cardiac remodeling in type 2 diabetes mellitus patients: focus on sodium-glucose cotransporter-2 inhibitor - Berezin, A. E.; Berezin, O. A.; Березін, Олександр Євгенійович (My University, 2022)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors have been recently approved by world-reputed medical associations as a milestone of class A management of heart failure (HF) with reduced ejection fraction (HFrEF) after pooling strong evidence (mainly for dapagliflozin or empagliflozin) regarding their beneficial impact on total occurrences of cardiovascular deaths and hospitalizations for HF in patients with and without type 2 diabetes mellitus (T2DM). Having a wide range of profile of favorable pleiotropic effects on heart, vessels, and kidney, SGLT2 inhibitors probably have a class-specific tissue protective ability, while its exact molecular mechanism has not been clearly understood yet. However, whether these agents retain their potency to reverse adverse cardiac remodeling remains unclear. The review elucidates the role of SGLT2 inhibitors in the potential reversibility of cardiac remodeling in connection with the improvement of clinical outcomes among T2DM patients having HF. Herein, we discussed the effects of SGLT2 inhibitors on cardiac structure and hemodynamics in T2DM patients. We revealed that empagliflozin had sufficient benefits in alleviating the adverse cardiac remodeling in HFrEF individuals than other SGLT2 inhibitors. These findings can open a new vision for the optimization of HF therapy in the near future.
Keywords: heart failure (HF); sodium-glucose cotransporter-2 inhibitors (SGLT2); adverse cardiac remodeling; type 2 diabetes mellitus (T2DM)